2021
DOI: 10.3390/ijerph182212161
|View full text |Cite
|
Sign up to set email alerts
|

Referral Patterns in Oral Medicine: A Retrospective Analysis of an Oral Medicine University Center in Southern Italy

Abstract: Referral of a patient from one healthcare provider to another is an important part of the medical practice. The aim of this study was to analyze the referral process to the Oral Medicine Unit in a university-based tertiary center in Southern Italy. A chart review of new referrals to the Oral Medicine Unit during a 24-month period was conducted. The following data were recorded: demographic characteristics, medical history, number of physicians seen prior to Oral Medicine assessment, referral source, diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…This resulted in increased patient anxiety and distress due to a lack of diagnosis and treatment. This is in line with previous studies, which reported that patients with oral mucosal lesions underwent unnecessary tests and were not diagnosed or misdiagnosed despite being seen by multiple clinicians 5,6 . This resulted in diagnostic delays, which could worsen the prognosis for many conditions or at least affect the patients' oral health‐related quality of life 5 …”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This resulted in increased patient anxiety and distress due to a lack of diagnosis and treatment. This is in line with previous studies, which reported that patients with oral mucosal lesions underwent unnecessary tests and were not diagnosed or misdiagnosed despite being seen by multiple clinicians 5,6 . This resulted in diagnostic delays, which could worsen the prognosis for many conditions or at least affect the patients' oral health‐related quality of life 5 …”
Section: Discussionsupporting
confidence: 89%
“…diagnostic delays, which could worsen the prognosis for many conditions or at least affect the patients' oral healthrelated quality of life. 5 The patient in the first case had only a mild burning sensation but was distressed by the recurrent nature of the lesions and the lack of diagnosis even after a biopsy. Most BMG lesions are asymptomatic, and despite being a benign lesion, BMG triggers concerns for patients and causes diagnostic difficulties for professionals, as the diagnosis is entirely based on the history and clinical presentation, and a tissue biopsy is unnecessary.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations